COUNTRY IMAGE IN MOVIES: A STUDY ON “HOLOGRAM FOR THE KING” MOVIE - Duygu Dersan Orhan; Elif Eşiyok (Selçuk İletişim)
Movies are generally used as a tool for disseminating country’s image. In the relevant literature, there is a general understanding that the Arabs are dehumanized and depicted in negative ways in the Hollywood movies. However, “Hologram for the King” has a more realistic and less biased approach with its focus on both the negative and the positive aspects of Saudi Arabia and its people. The aim of this study, is to analyze the representation of Saudi Arabia and its people in the Hollywood movie “Hologram for the King”. Content analysis method is used for the analysis. The findings of the study indicated that, the total duration of the country image in the movie is 28.9 minutes. Political and social character of the country and capacities/competencies of the country were found to have the highest percentage. This result, reflects that movies are and important tool of communication for the country image.